PENGUATAN PENDIDIKAN KARAKTER MELALUI SOSIALISASI 4A (ANTI-KORUPSI, ANTI-PERUNDUNGAN, ANTI-INTOLERANSI, DAN ANTI-KEKERASAN SEKSUAL) DI SMPN 1 SITUBONDO - Aurelia Ramadhani Winarta (Jurnal Abdi Publik (JAP), 2026)
The 4A Socialization Program (Anti-Corruption, Anti-Bullying, Anti-Intolerance, and Anti-Sexual Violence) at SMPN 1 Situbondo was implemented as an effort to strengthen character education and to respond to the high incidence of violence in the school environment. Based on data collected during 2023–2024, a total of 1,745 cases of violence were recorded, including physical violence, psychological violence, bullying, intolerance, sexual violence, and other forms of misconduct, indicating the need for targeted interventions to instill values of integrity, empathy, tolerance, and anti-violence behavior in students. Through socialization sessions, educational video screenings, interactive discussions, and case analyses, this program aims to enhance students’ understanding of the 4A values and encourage positive behavioral change. The results show increased student awareness in rejecting bullying, respecting differences, maintaining honesty, and reporting acts of violence within the school. Thus, the 4A Socialization Program serves as a strategic step in creating a safe, inclusive, and character-driven learning environment at SMPN 1 Situbondo.